Child Marriage, Family Law, and Religion : An Introduction to the Fall 2015 Issue - Wodon, Quentin (Taylor and Francis, 2015)
Child marriage, defined as marrying before the age of 18, is a practice that affects mostly girls and often leads to violations of human rights for the girls who have to marry early. UNICEF estimates that 140 million girls will marry early in the next decade or up to 40,000 per day. Especially when marriage takes place very early (well below the age of 18), it profoundly affects a girl’s life through lowering her education and future earnings prospects. It may also lead to health complications, compromised psychological wellbeing, intimate partner violence, and a lack of participation and voice for the girls in their community and society at large.